DEVELOPMENT OF PROFESSIONAL COMPETENCES OF STUDENTS (American Journal of Pedagogical and Educational Research, 2023)
The formal structure of the system of professional pedagogical training in higher education consists of a set of teachers, teaching aids, students and teaching technologies. This article discusses the importance of developing the professional competence of teachers.